The prognostic value of fluorodeoxyglucose positron emission tomography metabolic tumor volume in solitary colorectal liver metastasis. Issue 5 (25th July 2016) - Huang, Yi‐Tung T; Park, Joomann; Chong, Shanley; Hugh, Thomas J; Ng, Weng Leong; Lin, Michael
Abstract: Background: Management of colorectal liver metastasis (CRLM) is evolving but surgery remains the most effective treatment in improving survival. Optimal preoperative patient selection is important and semiquantitative F‐18 fluorodeoxyglucose positron emission tomography (PET) parameters may provide valuable prognostic information. Methods: Sixty‐one patients with solitary CRLM as first site of distant dissemination and preoperatively staged with PET were retrospectively studied. Various semiquantitative PET parameters, pathological size of the hepatic lesion and clinical variables were correlated with survival outcome. The data were analyzed with nonparametric Kruskal–Wallis test and univariate Cox regression. Kaplan–Meier estimates of overall survival and disease‐free survival (DFS) were log‐rank tested. Results: Mean follow‐up for the 61 subjects was 48 months. The 1‐ and 3‐year survival rates were 98.7% and 72.2%. The median DFS was 16 months with recurrence in 10 (16.4%) patients following surgery. Univariate analysis found a statistically significant increased risk of death for higher mean PET tumor diameter (hazard ratio [HR] 2.95, P = 0.014), mean metabolic tumor volume (HR 3.0, P = 0.009) and median pathological size of hepatic lesion (HR 2.97, P = 0.022). Maximum standardized uptake value of the liver metastasis and calculated standardized uptake value ratio between tumor and normal liver parenchyma (tumor background ratio) were not predictive of overall survival. None of the PET parameters or clincopathological variables statistically correlated with DFS. Conclusion: Semiquantitative PET variables are potentially valuable prognostic biomarkers in CRLM. Volumetric data like metabolic tumor volume enable better estimation of tumor burden and its utility may improve preoperative risk stratification and optimize outcome.